DISTRIBUSI LARVA NYAMUK AEDES DI LINGKUNGAN SEKOLAH - F. Dewi Kusumowardani (Dian Nuswantoro Semarang, 2019)
The proportion of dengue events is still dominated by school-age children and notall school environments are free of larvae. The purpose of this study is todescribe the larvae (SICENTIK) student activities against school larvae freenumbers, student home environments and school buffers in Srondol CommunityHealth Center. This type of research is observational with cross sectional design.The study sample was the total population of all 4th to 9th grade students in allelementary and junior high schools in the Srondol Community Health Centerwhere the number of elementary schools was 15 and 6 junior high schools with2518 elementary school students and 2575 junior high school students. Datawere analyzed by descriptive analysis. The results of the study revealed that 81%of schools had participated in implementing Sicentik but there were still 9.5% ofschools that had not implemented Sicentik and 9.5% of schools had participatedbut the ABJ results were still below the standard to be free from transmission ofDHF. Container index in the school environment is 90.5% and there are still 19%ABJ in the home environment of students who are vulnerable to denguetransmission. There are still schools that have not participated in theimplementation of the potential for potential transmission of dengue in the schoolenvironment. Monitoring the implementation of Sicentik activities can improve theABJ in schools and the home environment.Keywords: Sicentik, Larva Distribution, School Buffers